Evaluation of the Ability of Early Childhood Education Teachers to Face Social and Cultural Changes - Hasanah, Nailul; Purnomo, Halim; Putri, Mega Safita (Tahta Media Group, 2025)
This study aims to evaluate the ability of PAUD RA Darul Fikri Bringin teachers in responding to the dynamics of social and cultural change, covering four dimensions: pedagogical competence and digital literacy, internalization of religious values, collaboration with families and communities, and the use of institutional supervision as a means of professional development. The research uses a qualitative approach with a field study design. Data were collected through structured participatory observation (12 sessions, 60–90 minutes per session), semi-structured in-depth interviews (45–60 minutes per informant) with 6 teachers, 1 principal, and 4 guardians, and documentation studies. Data analysis model which includes data condensation, data presentation, conclusion drawn, and verification, with data validity guaranteed through triangulation of sources and methods as well as member checks. The results show that teachers have adequate basic pedagogical competencies and a strong commitment to inculcate Islamic values through daily habits, but the digital literacy gap between teachers is quite significant—only 2 out of 6 teachers actively use digital media in learning. Collaboration with families is going quite well through parenting programs and liaison books, although some parents are still passive. Institutional supervision is still administrative and has not encouraged substantive pedagogical reflection. The research concludes that RA Darul Fikri Bringin teachers have the potential to be a bridge between tradition and modernity, but require strengthening through the development of digital-local training modules, coaching-based supervision, and integrative curriculum guidelines based on local cultural wisdom.